Utilization of Artificial Intelligence in Islamic Religious Education: A Case Study of Darul Hikmah Islamic Boarding School - Hidayatullah, Ahmad Syarif; Sholikah, Mar’atus; Abidin, Zainal (Journal of English Language and Education, 2025)
The development of information and communication technology (ICT) has brought significant changes in the world of education, especially with the presence of Artificial Intelligence (AI). Intelligence (AI). This study aims to identify opportunities and challenges of implementing AI in Islamic religious education at the Darul Hikmah Kyai Abdan Islamic Boarding School, and to formulate strategies to overcome existing obstacles. The research method used is qualitative with a case study approach and library research, complemented by interviews and observations. The results of the study indicate that AI has great potential in personalizing learning, interactive evaluation, analyzing learning patterns, and increasing the efficiency of Islamic boarding school administration. At the Darul Hikmah Kyai Abdan Islamic Boarding School, AI has been implemented in teaching the Qur'an and hadith , as well as managing administration. However, this implementation faces challenges such as limited technological infrastructure, readiness of teaching staff, financial resources, and lack of AI content relevant to Islamic education. This study recommends solutions such as providing technological infrastructure, training of teaching staff, alternative funding, and developing AI content based on Islamic values. With the right strategy, AI can be optimized to improve the quality of Islamic religious education in Islamic boarding schools.